2015
DOI: 10.1080/13632469.2015.1027019
|View full text |Cite
|
Sign up to set email alerts
|

Earthquake Damage Analysis of Concrete Gravity Dams: Modeling and Behavior under Near-Fault Seismic Excitations

Abstract: In the near-fault region of an earthquake, ground motions are strongly affected by complex mechanisms and can be significantly different from typical far-fault ground motions. Although the significance of near-fault ground motions has been widely recognized, its influence on the earthquake performance of concrete gravity dams has not yet been fully quantified. This article investigates the effects of near-fault ground motions on the nonlinear seismic response behavior of concrete gravity dams. In particular, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…centers around modeling a concrete gravity dam, with Koyna Dam serving as a representative example. This dam has been a subject of study in numerous research papers, highlighting the significance of modeling assumptions in influencing damage intensity, failure patterns, and crack propagation schemes 4–19 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…centers around modeling a concrete gravity dam, with Koyna Dam serving as a representative example. This dam has been a subject of study in numerous research papers, highlighting the significance of modeling assumptions in influencing damage intensity, failure patterns, and crack propagation schemes 4–19 …”
Section: Discussionmentioning
confidence: 99%
“…However, several studies demonstrate a direct correlation between structural quantities (e.g., damage index) and the modeling of dynamic dam-foundation interactions under near-fault pulse-like ground motions. 16,[22][23][24][25][26][27][28][29][30][31][32][33] These studies underscore the critical role of engineering demand parameters (EDPs) in comparing pulse-like and nonpulse motions. For instance, Yazdani and Alembagheri 27 demonstrated that fragility curves based on crest displacement and neck damage index are very close for pulse-like and nonpulse motions, with notable distinctions observed in the case of the base damage index.…”
Section: Seismic Response Of the Dammentioning
confidence: 99%
See 1 more Smart Citation
“…Design flaws and bridge degradation contribute to the damage. Seismic design is crucial for reinforced concrete bridges to withstand earthquakes and ensure safety [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Bayraktar A et al (2010) discussed the dynamic response of the reservoir zone to the gravity dam under the action of a near-fault pulse earthquake, and studied the nonlinear dynamic response of the dam-reservoir-foundation system under the action of near-fault ground motions. Akkose M et al (2010) etc Studied the nonlinear dynamic response of the dam-reservoir-sediment-foundation system to near-fault ground motions and far-fault ground motions, revealing the change law of dam crest displacement and plastic deformation caused by near-fault ground motions ;Wang Gaohui et al (2014) conducted a comparative analysis of the effects of near-fault directivity pulse and far-fault ground motions on the cumulative damage characteristics of concrete gravity dams; Huang J (2015) studied the influence of the spatial variability of near-site vibration on the cumulative damage effect of gravity dams; Yazdani Y et al (2017) studied the nonlinear seismic response of gravity dams under the action of near-fault ground motions and equivalent pulses; Gorai S et al (2021) studied the seismic behavior of aged concrete gravity dams to near source and far source ground motions. However, the above research only considers the damage distribution of the dam body, ignoring the damage and failure of the foundation rock mass under the action of the earthquake.…”
Section: Introductionmentioning
confidence: 99%